Neuromorphic transistor taking lithium niobate or lithium tantalate single crystal as gate medium and preparation method thereof
By epitaxially growing ZnSnO3 films on a single crystal LiNbO3 or LiTaO3 substrate and directly depositing single crystal lithium niobate or lithium tantalate films as gate dielectric layers, the problems of easy introduction of FeFET film preparation, complex process and high cost in the prior art are solved, and the preparation and process of high-quality films are achieved.
Patent Information
- Application Number
- CN202411509555.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, the preparation of FeFET films based on single crystal lithium niobate or lithium tantalate has problems such as easily introducing defects, cumbersome process and high cost.
Single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001) is used as the substrate, and ZnSnO3 film is epitaxially grown on its surface as the bottom gate electrode, and then a single crystal lithium niobate or lithium tantalate film is directly deposited as the gate dielectric layer, so that the film is generated by physical vapor deposition.
It effectively avoids the interface stress caused by lattice mismatch, reduces the introduction of defects, and reduces the use of buffer layers, simplifies process, reduces costs, and improves film quality.
Smart Images

Figure CN119603993A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a neuromorphic transistor using lithium niobate or lithium tantalate single crystal as a gate dielectric and a preparation method thereof, and belongs to the technical field of semiconductor devices. Background Art
[0002] With the rapid development of information technology, people's quality of life has been further improved, but massive amounts of data are still processed by the von Neumann architecture. This traditional computing architecture with separate storage and computing units cannot achieve simultaneous acquisition of instructions and data, and also requires frequent memory access operations, resulting in low data processing efficiency and high energy consumption.
[0003] Neuromorphic transistors are a new type of device inspired by the efficient and low-power information processing capabilities of biological nervous systems. Their purpose is to work like the brain by simulating synaptic plasticity. These devices have excellent non-volatility and can perform data calculations while storing data. Therefore, compared with traditional transistors, neuromorphic transistors have lower operating energy consumption, and efficient parallel computing also greatly improves the fault tolerance of system calculations. At present, neuromorphic transistors have been derived into various types according to different materials and working mechanisms, and have shown strong application prospects in various fields. Among them, ferroelectric field effect transistors (FeFETs) can achieve non-volatile switching and storage of information due to the spontaneous polarization characteristics of ferroelectric materials and the ability to modulate the conductivity of the semiconductor channel under the action of an external electric field. In addition, due to the low operating voltage and stable electrical performance of FeFETs, large-scale integration can be achieved, which is suitable for the field of neuromorphic engineering.
[0004] Single crystal lithium niobate or lithium tantalate is a ferroelectric material whose polarization state can change under the action of an external electric field and can still maintain its state after the electric field is removed. This property makes single crystal lithium niobate or lithium tantalate have great application value in the field of microelectronic devices. At room temperature, the spontaneous polarization of single crystal lithium niobate can reach 70~80 μm / cm 2, and has a high Curie temperature (1210 ℃), which allows the material to maintain ferroelectric properties in high temperature environments. It is worth noting that FeFETs based on single-crystalline lithium niobate or lithium tantalate thin films have extremely low leakage current, excellent current switching ratio and ultra-low subthreshold swing, so they have the potential for low-power and high-efficiency computing. In addition, the ferroelectric domain wall of single-crystalline lithium niobate or lithium tantalate can be used as a channel for information transmission. By controlling the position and polarization state of the domain wall, information storage and processing can be achieved. This mechanism is similar to the way in which synapses in biological nervous systems transmit information. Therefore, single-crystalline lithium niobate or lithium tantalate ferroelectric transistors have important application potential in neuromorphic computing systems that simulate the working mechanism of the human brain. At the same time, single-crystalline lithium niobate or lithium tantalate has excellent electro-optical effect, extremely low light absorption loss and nonlinear optical properties, and is often regarded as an ideal material for optoelectronic devices such as electro-optical modulators, optical waveguides and lasers. FeFETs based on single-crystal lithium niobate or lithium tantalate are also used in artificial visual synapses to simulate biological visual perception. Therefore, it is of great significance to epitaxially grow single-crystal lithium niobate or lithium tantalate films on substrates with high quality to prepare neuromorphic transistors with ferroelectric properties.
[0005] At present, the preparation of single-crystal lithium niobate or lithium tantalate thin films usually adopts crystal ion slicing technology (CIS). CIS is a technology used to manufacture high-quality single-crystal thin films, but ion implantation and heat treatment are required in the process. + or He + When injected into the bulk material, a buried damage layer will be formed, and a single crystal film can only be obtained after rapid thermal annealing (RTP). However, these steps may introduce defects such as lattice damage and increased surface roughness. Controlling these defects is crucial to obtaining high-quality films. Therefore, chemical mechanical polishing (CMP) is often required to reduce the roughness of the film. The process is cumbersome and the investment cost is high. Summary of the invention
[0006] In order to solve the problems in the existing technology of FeFET based on single crystal lithium niobate or lithium tantalate, such as easy introduction of defects, complicated process and high cost in the preparation technology of single crystal lithium niobate or lithium tantalate film, the present application provides a technical solution and a corresponding preparation method for a neuromorphic transistor with lithium niobate or lithium tantalate single crystal as the gate dielectric. (0001) oriented lithium niobate or lithium tantalate is selected as a specific substrate, and a ZnSnO3 film is epitaxially grown on its surface as a bottom gate electrode, so that single crystal lithium niobate or lithium tantalate film can be directly deposited as a gate dielectric layer. Through such specific structural selection and matching, the occurrence of lattice mismatch is effectively avoided, and the introduction of buffer layer is also reduced. In addition, the formation of the film can be carried out by physical vapor deposition, which has higher safety and lower process cost.
[0007] This application adopts the following technical solutions: According to one aspect of the present application, there is provided a neuromorphic transistor using lithium niobate or lithium tantalate single crystal as a gate dielectric, comprising a substrate layer, a bottom gate electrode layer, a gate dielectric layer and a patterned electrode assembly arranged from top to bottom; The material of the substrate layer includes single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001); The bottom gate electrode layer includes a single crystal ZnSnO3 thin film; The gate dielectric layer includes a single crystal LiNbO3 or a single crystal LiTaO3 thin film.
[0008] Single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001) refers to lithium niobate or lithium tantalate with a crystal plane index of (0001), which has high purity and good crystal integrity, which helps to ensure the quality and performance of the epitaxial layer.
[0009] Single crystal ZnSnO3 has the same structure as the preferred substrate material, which can effectively avoid interface stress caused by lattice mismatch and reduce defects.
[0010] The substrate layer, bottom gate electrode layer and gate dielectric layer arranged from top to bottom are obtained by sequentially depositing the bottom gate electrode layer and the gate dielectric layer on the substrate layer by physical vapor deposition method.
[0011] In one embodiment, the thickness of the bottom gate electrode layer is 100 nm to 400 nm.
[0012] In one embodiment, the gate dielectric layer has a thickness of 100 nm to 2 μm.
[0013] In one embodiment, the patterned electrode assembly includes a channel layer, a source electrode, and a drain electrode; The channel layer is located between the source and the drain.
[0014] In one embodiment, the material of the channel layer is selected from N-type semiconductor materials.
[0015] In one embodiment, the N-type semiconductor material is preferably IGZO oxide semiconductor material.
[0016] In one embodiment, the source and the drain are both low work function metal electrodes.
[0017] In one embodiment, the material of the low work function metal electrode is selected from at least one of Au, Cr, Ni, and Pt. The material of the source and drain is selected to obtain a metal electrode with a lower work function.
[0018] According to another aspect of the present application, a method for preparing the above-mentioned neuromorphic transistor using lithium niobate or lithium tantalate single crystal as gate dielectric is provided, comprising the following steps: Providing a substrate layer including single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001) material; A bottom gate electrode layer including a single crystal ZnSnO3 thin film is grown on the substrate layer by physical vapor deposition, and then a gate dielectric layer including a single crystal LiNbO3 or a single crystal LiTaO3 thin film is grown on the bottom gate electrode layer; A patterned electrode assembly is fabricated on the gate dielectric layer by sputtering.
[0019] In one embodiment, the conditions for growing a single crystal include: preheating a substrate under vacuum conditions, then heat treating the substrate under oxygen pressure conditions, then performing physical vapor deposition on the substrate to obtain a target thin film and then performing in-situ annealing; The substrate is a substrate layer or a substrate layer deposited with a bottom gate electrode layer.
[0020] In one embodiment, the preheating conditions include: heating the substrate to 450°C to 500°C at a heating rate of 5°C / min to 20°C / min and then maintaining the temperature for 3 min to 5 min, In one embodiment, the oxygen pressure condition includes: continuously introducing oxygen with an oxygen pressure of 20 Pa to 30 Pa; In one embodiment, the heat treatment conditions include: heating the substrate to 600°C to 700°C and maintaining the temperature for 3 min to 5 min, In one embodiment, the in-situ annealing conditions include: adjusting the oxygen supply to reach atmospheric pressure, maintaining the heat treatment temperature for 30 min to 60 min, then cooling to 350°C to 400°C, stopping the oxygen supply, and naturally cooling under vacuum conditions.
[0021] In one embodiment, the physical vapor deposition is selected from pulsed laser deposition; The conditions of pulsed laser deposition include: the laser energy of the laser is 120 mJ ~140 mJ, and the frequency is 1 Hz ~3 Hz.
[0022] In one embodiment, the process of making a patterned electrode assembly includes: Using N-type semiconductor material as target, radio frequency sputtering deposition forms a channel; Using low work function metal as the target, DC sputtering deposition is performed on both sides of the channel to form the source and drain.
[0023] In one embodiment, the physical vapor deposition process also includes pre-sputtering for 5 min to 10 min to remove impurities on the surface of the target material, and the target material is single crystal ZnSnO3, single crystal LiNbO3 or single crystal LiTaO3. The beneficial effects of this application include: The neuromorphic transistor provided in the present application adopts lithium niobate or lithium tantalate single crystal as the gate dielectric of FeFET. Compared with other ferroelectric materials, single crystal lithium niobate or lithium tantalate exhibits better ferroelectric properties, which can help FeFET reduce the operating voltage while reducing the generation of leakage current. The gate electrode material single crystal ZnSnO3 film used in the transistor has the same structure as the single crystal gate dielectric material and substrate material, which ensures lattice matching between single crystal films, thereby reducing the introduction of buffer layers.
[0024] In the preparation process of the neuromorphic transistor provided in the present application, single crystal lithium niobate (0001) or lithium tantalate (0001) is used as a substrate, and a lattice-matched single crystal ZnSnO3 film can be epitaxially grown by pulsed laser deposition technology, and then a Z-cut single crystal lithium niobate or lithium tantalate film can be further epitaxially grown on the single crystal ZnSnO3 film. The single crystal ZnSnO3 film in the present application can not only be used for the growth of Z-cut single crystal lithium niobate or lithium tantalate films, but also has good electrical conductivity and is suitable for the electrode structure of the device. In addition, the single crystal ZnSnO3 film has high light transmittance and chemical stability, which is beneficial to optoelectronic neuromorphic applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the structure of the neuromorphic transistor of this application.
[0026] Figure 2 This is a schematic diagram of the process flow of the method for preparing the neuromorphic transistor of the present application.
[0027] Figure ID 1. Substrate layer; 2. Bottom gate electrode layer; 3. Gate dielectric layer; 4. Channel; 5. Source; 6. Drain. DETAILED DESCRIPTION
[0028] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0029] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0030] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0031] In the existing technology of FeFET based on single crystal lithium niobate or lithium tantalate used in artificial visual synapses, it is necessary to epitaxially grow single crystal lithium niobate or lithium tantalate thin films on the substrate with high quality to prepare neuromorphic transistors with ferroelectric properties. However, in the existing technology of preparing single crystal lithium niobate or lithium tantalate thin films, the crystal ion slicing technology (CIS) process usually involves ion implantation and heat treatment, which will form a buried damage layer and may introduce defects such as lattice damage and increased surface roughness. Controlling these defects is crucial to obtaining high-quality films. Therefore, chemical mechanical polishing (CMP) is often required to reduce the roughness of the film. The process is cumbersome and the investment cost is high. In response to the above-mentioned problems, the present application provides a neuromorphic transistor using lithium niobate or lithium tantalate single crystal as a gate dielectric and a method for preparing the same. Single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001) is used as a substrate, and a single crystal ZnSnO3 film is epitaxially grown thereon, and then a single crystal LiNbO3 film or a LiTaO3 film can be directly deposited as a gate dielectric layer. This method avoids the occurrence of lattice mismatch and also reduces the introduction of a buffer layer in the prior art.
[0032] In one embodiment, a neuromorphic transistor using lithium niobate or lithium tantalate single crystal as a gate dielectric includes a substrate layer, a bottom gate electrode layer, a gate dielectric layer, and a patterned electrode assembly arranged from top to bottom; The material of the substrate layer includes single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001); The bottom gate electrode layer includes a single crystal ZnSnO3 thin film; The gate dielectric layer includes a single crystal LiNbO3 or a single crystal LiTaO3 thin film.
[0033] Single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001) refers to lithium niobate or lithium tantalate with a crystal plane index of (0001), which has high purity and good crystal integrity, which helps to ensure the quality and performance of the epitaxial layer.
[0034] The single crystal ZnSnO3 has the same structure as the preferred substrate material, which can effectively avoid the interface stress caused by lattice mismatch and reduce defects. The single crystal ZnSnO3 layer has good conductivity and is suitable for the electrode structure of the device. The single crystal ZnSnO3 film has high transmittance and chemical stability, which is beneficial to optoelectronic neuromorphic applications.
[0035] The substrate layer, bottom gate electrode layer and gate dielectric layer arranged from top to bottom are obtained by sequentially depositing the bottom gate electrode layer and the gate dielectric layer on the substrate layer by physical vapor deposition method.
[0036] In one embodiment, the thickness of the bottom gate electrode layer is 100 nm to 400 nm.
[0037] In one embodiment, the gate dielectric layer has a thickness of 100 nm to 2 μm.
[0038] In one embodiment, the patterned electrode assembly includes a channel layer, a source electrode, and a drain electrode; The channel layer is located between the source and the drain.
[0039] In one embodiment, the material of the channel layer is selected from N-type semiconductor materials; In one embodiment, the N-type semiconductor material is preferably IGZO oxide semiconductor material.
[0040] In one embodiment, the source and drain are both low work function metal electrodes. In one embodiment, the material of the low work function metal electrode is selected from at least one of Au, Cr, Ni, and Pt. The material of the source and drain is selected to obtain a metal electrode with a lower work function.
[0041] Single crystal lithium niobate or lithium tantalate is used as the gate dielectric of FeFET. Compared with other ferroelectric materials, single crystal lithium niobate or lithium tantalate exhibits better ferroelectric properties, which can help FeFET reduce the operating voltage while reducing the generation of leakage current.
[0042] In one embodiment, the structure of the neuromorphic transistor using lithium niobate or lithium tantalate single crystal as the gate dielectric is as follows: Figure 1 As shown, it includes a bottom gate electrode 2, a gate dielectric layer 3, and a patterned electrode assembly deposited sequentially from bottom to top on a substrate layer 1. The substrate layer 1 is single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001); the bottom gate electrode layer 2 is single crystal ZnSnO3; the gate dielectric layer 3 is single crystal LiNbO3 or single crystal LiTaO3, which is obtained by epitaxial growth; the electrode group includes a channel 4, a source 5, and a drain 6, the channel 4 is an IGZO oxide semiconductor material, and the electrode is Au.
[0043] The thin film growth method in the device structure of the neuromorphic transistor using lithium niobate or lithium tantalate single crystal as the gate dielectric in the present application is a physical vapor deposition method, which has higher safety and lower process cost. The preparation method of the neuromorphic transistor using lithium niobate or lithium tantalate single crystal as the gate dielectric includes the following steps: Providing a substrate layer including single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001) material; A bottom gate electrode layer including a single crystal ZnSnO3 thin film is grown on the substrate layer by physical vapor deposition, and then a gate dielectric layer including a single crystal LiNbO3 or a single crystal LiTaO3 thin film is grown on the bottom gate electrode layer; A patterned electrode assembly is fabricated on the gate dielectric layer by sputtering.
[0044] In one embodiment, a method for preparing a neuromorphic transistor using lithium niobate or lithium tantalate single crystal as a gate dielectric is as follows: Figure 2 As shown, the specific steps include: Step 1. The single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001) substrate layer is ultrasonically cleaned with acetone, alcohol, and deionized water in sequence, and then dried with high-purity nitrogen; Step 2. Epitaxially grow single crystal ZnSnO3, single crystal LiNbO3 or single crystal LiTaO3 on the substrate layer in sequence by pulsed laser deposition, as the bottom gate electrode layer and gate dielectric layer respectively, and perform annealing treatment to avoid leakage current increase caused by film defects. The quality and thickness of the bottom gate electrode layer and gate dielectric layer are jointly determined by working pressure, growth temperature, laser energy, time and other factors; Step 3. Sputter the patterned channel and source-drain electrodes on the gate dielectric layer by magnetron sputtering. The channel material is preferably IGZO, which is obtained by radio frequency sputtering. The source-drain electrodes are preferably Au, which are obtained by direct current sputtering.
[0045] In one embodiment, the conditions for growing a single crystal include: preheating a substrate under vacuum conditions, then heat treating the substrate under oxygen pressure conditions, then performing physical vapor deposition on the substrate to obtain a target thin film and then performing in-situ annealing; The substrate is a substrate layer or a substrate layer deposited with a bottom gate electrode layer.
[0046] In one embodiment, the preheating conditions include: heating the substrate to 450°C to 500°C at a heating rate of 5°C / min to 20°C / min and then maintaining the temperature for 3 min to 5 min; In one embodiment, the oxygen pressure condition includes: continuously introducing oxygen with an oxygen pressure of 20 Pa to 30 Pa; In one embodiment, the heat treatment conditions include: heating the substrate to 600°C to 700°C and maintaining it for 3 min to 5 min; In one embodiment, the in-situ annealing conditions include: adjusting the oxygen supply to reach atmospheric pressure, maintaining the heat treatment temperature for 30 min to 60 min, then cooling to 350°C to 400°C, stopping the oxygen supply, and naturally cooling under vacuum conditions.
[0047] In one embodiment, the physical vapor deposition is selected from pulsed laser deposition; The conditions of pulsed laser deposition include: the laser energy of the laser is 120 mJ ~140 mJ, and the frequency is 1 Hz ~3 Hz.
[0048] In the present application, when single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001) is used as the substrate layer, a lattice-matched single crystal ZnSnO3 thin film can be epitaxially grown by pulsed laser deposition technology, and then a Z-cut single crystal LiNbO3 or single crystal LiTaO3 thin film can be further epitaxially grown on the single crystal ZnSnO3 thin film.
[0049] In one embodiment, the process of making a patterned electrode assembly includes: Using N-type semiconductor material as target, radio frequency sputtering deposition forms a channel; Using low work function metal as the target, DC sputtering deposition is performed on both sides of the channel to form the source and drain.
[0050] In one embodiment, the physical vapor deposition process further includes pre-sputtering for 5 min to 10 min to remove impurities on the surface of the target material, and the target material is single crystal ZnSnO3, single crystal LiNbO3 or single crystal LiTaO3.
[0051] In one embodiment, the method for preparing a neuromorphic transistor using lithium niobate or lithium tantalate single crystal as a gate dielectric specifically comprises the following steps: Step 1. The double-polished single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001) substrate layer 1 is ultrasonically cleaned with acetone, alcohol, and deionized water for 10 to 20 minutes in sequence, and dried with high-purity nitrogen at 60 to 80 ° C to prevent moisture residue; Step 2. Place the cleaned substrate into the growth chamber of the pulsed laser system, adjust the distance between the sample stage and the target to 40 mm, and replace the target with a single crystal ZnSnO3 target; Step 3. Preparation of bottom gate electrode: Use mechanical pump and molecular pump to reduce the vacuum degree of the growth chamber to 10 -6Pa. Raise the temperature of the sample stage to 500 ℃ at a heating rate of 15 ℃ / min. After the sample stage reaches 500 ℃, maintain it for 3~5 min. Open the oxygen valve, control the gas flow rate and the shut-off baffle to keep the oxygen pressure at 30 Pa. After the working pressure is stabilized, raise the temperature of the sample stage to ~600 ℃ and maintain it for 3~5 min. After the substrate on the sample stage is stable, open the target baffle and pre-sputter for 5 min to remove impurities on the surface of the target. Then set the laser energy of the laser to 130 mJ and the frequency to 1 Hz. After the settings are completed, start the laser and open the sample baffle to start deposition. After the end, turn off the laser and anneal the sample in situ at atmospheric pressure for 30 minutes. After the annealing is completed, slowly reduce the temperature of the sample stage to 400 ℃. Close the oxygen valve and reduce the pressure in the room to 10 -3 After Pa, the vacuum is broken. The sample stage is turned off to heat the sample, and the sample is allowed to cool to room temperature naturally to obtain a high-quality single-crystalline ZnSnO3 film; Step 4. Prepare the gate dielectric layer: Replace the target with a single crystal LiNbO3 target and perform in-situ deposition. First, reduce the vacuum level in the growth chamber to 10 -6 Pa. Raise the temperature of the sample stage to 500 ℃ at a heating rate of 5~10 ℃ / min. After the sample stage reaches 450 ℃, maintain it for 3~5 min. Open the oxygen valve, control the gas flow rate and the shut-off baffle to keep the oxygen pressure at 20 Pa. After the working pressure is stabilized, raise the temperature of the sample stage to ~550 ℃ and maintain it for 3~5 min. After the substrate on the sample stage is stable, open the target baffle and pre-sputter for 5 min to remove impurities on the surface of the target. Then set the laser energy of the laser to 130 mJ and the frequency to 2 Hz. After the settings are completed, start the laser and open the sample baffle to start deposition. After the end, turn off the laser and anneal the sample in situ at atmospheric pressure for 30 min. After the annealing is completed, slowly reduce the temperature of the sample stage to 400 ℃. Close the oxygen valve and reduce the pressure in the room to 10 -3 After 300 Pa, the vacuum is broken. The sample stage is turned off for heating, and the sample is allowed to cool to room temperature naturally to obtain a single crystal LiNbO3 or single crystal LiTaO3 film that matches the single crystal ZnSnO3 film lattice; Step 5. After the sample reaches room temperature, take it out and put it into the growth chamber of the magnetron sputtering system. Adjust the distance between the sample stage and the target to 80 mm, replace the RF target with an IGZO target, and replace the DC target with an Au target for the preparation of the patterned electrode group; Step 6. Prepare the channel: Use mechanical pump and molecular pump to reduce the vacuum level of the growth chamber to 10 -3Pa or less. Open the argon valve, control the gas flow rate and the shut-off baffle, and keep the pressure in the growth chamber at 3 Pa. Set the RF power supply to 100 W, and turn on the power after the pressure stabilizes. After the glow stabilizes, reduce the pressure in the growth chamber to 0.5 Pa. Pre-sputter for 3 to 5 minutes to remove impurities on the surface of the IGZO target. Then rotate the sample stage, and control the speed at 8 to 15 rpm to ensure uniform growth of the channel. Finally, open the sample baffle and start depositing IGZO. A patterned channel can be obtained through a mask; Step 7. Prepare source and drain electrodes: After step 6, break the vacuum and take samples, replace the mask with the electrode pattern and reload the samples. The vacuum degree of the growth chamber is reduced to 10 -3 Pa or less. Introduce argon gas, control the gas flow rate and the cut-off baffle to keep the pressure in the growth chamber at 10 Pa. Set the DC power supply to 50 W, and turn on the power to reduce the pressure to 1 Pa. Remove impurities on the surface of the Au target by pre-sputtering. Open the sample baffle when the sample stage rotates at 10-20 rpm to obtain uniformly grown source and drain electrodes.
[0052] Example 1 Neuromorphic transistor using lithium niobate single crystal as gate dielectric Step 1. The double-polished single crystal LiNbO3 (0001) substrate layer 1 is ultrasonically cleaned with acetone, alcohol, and deionized water for 15 minutes in sequence, and dried with high-purity nitrogen in an environment with a hot nitrogen temperature of 60°C to prevent moisture residue.
[0053] Step 2. Place the cleaned substrate into the growth chamber of the pulsed laser system, adjust the distance between the sample stage and the target to 40 mm, and replace the target with a single crystal ZnSnO3 target.
[0054] Step 3. Preparation of bottom gate electrode: Use mechanical pump and molecular pump to reduce the vacuum degree of the growth chamber to 10 -6 Pa. Raise the temperature of the sample stage to 500 ℃ at a heating rate of 15 ℃ / min. After the sample stage reaches 500 ℃, maintain it for 5 minutes. Open the oxygen valve, control the gas flow rate and the shut-off baffle to keep the oxygen pressure at 30 Pa. After the working pressure is stabilized, raise the temperature of the sample stage to ~600 ℃ and maintain it for 5 minutes. After the substrate on the sample stage is stable, open the target baffle and pre-sputter for 5 minutes to remove impurities on the surface of the target. Then set the laser energy of the laser to 130 mJ and the frequency to 1 Hz. After the settings are completed, start the laser, open the sample baffle to start deposition, and the deposition thickness is 100nm. After the end, turn off the laser and anneal the sample in situ at atmospheric pressure for 30 minutes. After the annealing is completed, slowly reduce the temperature of the sample stage to 400 ℃. Close the oxygen valve and reduce the pressure in the room to 10 - 3The vacuum was broken after 30 0.5 Pa. The sample stage was turned off to heat the sample, and the sample was allowed to cool to room temperature naturally to obtain a high-quality single-crystalline ZnSnO3 film.
[0055] Step 4. Prepare the gate dielectric layer: Replace the target with a single crystal LiNbO3 target and perform in-situ deposition. First, reduce the vacuum level in the growth chamber to 10 -6 Pa. Raise the temperature of the sample stage to 450 ℃ at a heating rate of 20 ℃ / min. After the sample stage reaches 450 ℃, maintain it for 5 minutes. Open the oxygen valve, control the gas flow rate and the shut-off baffle to keep the oxygen pressure at 20 Pa. After the working pressure is stabilized, raise the temperature of the sample stage to 550 ℃ and maintain it for 5 minutes. After the substrate on the sample stage is stable, open the target baffle and pre-sputter for 5 minutes to remove impurities on the surface of the target. Then set the laser energy of the laser to 130 mJ and the frequency to 2 Hz. After the settings are completed, start the laser, open the sample baffle to start deposition, and the deposition thickness is 400nm. After the end, turn off the laser and anneal the sample in situ at atmospheric pressure for 30 minutes. After the annealing is completed, slowly reduce the temperature of the sample stage to 400 ℃. Close the oxygen valve and reduce the pressure in the room to 10 -3 After the vacuum is broken, the sample stage is turned off to heat the sample, and the sample is allowed to cool to room temperature naturally, thereby obtaining a single-crystalline LiNbO3 film that matches the single-crystalline ZnSnO3 film lattice.
[0056] Step 5. After the sample reaches room temperature, take it out and put it into the growth chamber of the magnetron sputtering system. Adjust the distance between the sample stage and the target material to 80 mm, and replace the RF target with an IGZO target and the DC target with an Au target for the preparation of the patterned electrode group.
[0057] Step 6. Preparation of the channel: Use a mechanical pump and a molecular pump to reduce the vacuum level of the growth chamber to 10 -3 Pa or less. Open the argon valve, control the gas flow rate and the shut-off baffle, and keep the pressure in the growth chamber at 3 Pa. Set the RF power supply to 100 W, and turn on the power after the pressure stabilizes. After the glow stabilizes, reduce the pressure in the growth chamber to 0.5 Pa. Pre-sputter for 5 minutes to remove impurities on the surface of the IGZO target. Then rotate the sample stage and control the speed at 10 rpm to ensure uniform growth of the channel. Finally, open the sample baffle and start depositing IGZO. A patterned channel can be obtained through a mask.
[0058] Step 7. Prepare source and drain electrodes: After step 6, break the vacuum and take samples, replace the mask with the electrode pattern and reload the samples. The vacuum degree of the growth chamber is reduced to 10 -3Pa or less. Argon gas was introduced, and the gas flow rate and the cut-off baffle were controlled to keep the pressure in the growth chamber at 10 Pa. The DC power supply was set to 50 W, and the pressure was reduced to 1 Pa after the power was turned on. Impurities on the surface of the Au target were removed by pre-sputtering. The sample baffle was opened under the condition of a sample stage rotation speed of 10 rpm to obtain a uniformly grown source and drain electrode.
[0059] Example 2 Neuromorphic transistor using lithium tantalate niobate single crystal as gate dielectric The preparation process is the same as that of Example 1, except that the single crystal LiNbO3 (0001) substrate layer is replaced by a single crystal LiTaO3 (0001) layer.
[0060] Example 3 Neuromorphic transistor using lithium tantalate niobate single crystal as gate dielectric The preparation process is the same as that in Example 1, the only difference is that the process of preparing the bottom gate electrode in step 3 adopts the magnetron sputtering method, and the conditions are: the RF power is set at 100 W, argon gas is introduced into the growth chamber, the pressure is controlled at 0.5 Pa, the sample stage speed is maintained at 8~15 rpm, and the deposition time is 15 min.
[0061] Comparative Example 1 Step 1. Implant He with energy of 300 keV on the surface of 500 μm~1 mm thick Z-cut single crystal LiNbO3 wafer + ions, the implantation volume is 8×10 16 cm -2 .
[0062] Step 2. After the injection, the metal electrode Cr / Au is deposited by magnetron sputtering, and then a layer of SiO2 is deposited on the surface of the metal electrode and the other wafer by PECVD to bond the substrate.
[0063] Step 3. Anneal the ion-implanted wafer at a high temperature of 250-300 °C to obtain a single-crystalline LiNbO3 film.
[0064] Step 4. The single crystal LiNbO3 film is subjected to RTA and CMP treatment to reduce surface defects and roughness.
[0065] Step 5. Prepare the channel and source-drain electrodes according to the operating steps of steps 5 to 7 in Example 1.
[0066] Comparative Example 1 uses the CIS process to obtain a single-crystal lithium niobate film, which requires high-energy ion implantation, followed by annealing and peeling to obtain the desired film thickness. The slicing process has a high process cost due to ion implantation and heat treatment. The subsequent CMP treatment also requires a lot of time and cost. In comparison, Examples 1-3 all use a physical vapor deposition method, which has a high deposition rate, lower cost, and is suitable for rapid preparation.
[0067] Comparative Example 2 The structure of the prepared ferroelectric transistor is similar to that of Example 1, except that in step 4, the single crystal LiNbO3 film is obtained by CIS, the deposition of IGZO is replaced by mechanical stripping transfer of MoS2 in the channel preparation, and a high-k dielectric layer HfO2 with a thickness of 8 nm is introduced between the gate dielectric and the channel by atomic layer deposition technology, and then the two-dimensional semiconductor material MoS2 is transferred to the surface of the high-k dielectric layer by mechanical stripping. The specific steps are: use transparent tape to stick the single crystal MoS2 block, stick the tape with MoS2 on the glass sheet for a period of time, and then tear it off by hand. At this time, the glass sheet is attached with less than 10nm of MoS2, and PDMS is placed on the glass sheet as a transition material. After a period of time, the two-dimensional single crystal MoS2 is positioned and transferred from the glass sheet to the dielectric layer HfO2, and a two-dimensional channel is obtained. However, compared with Example 1, this preparation scheme for obtaining the channel is difficult to control the thickness and size of the material, has low controllability, and is difficult to achieve standardized and large-scale production.
[0068] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A neuromorphic transistor using lithium niobate or lithium tantalate single crystal as gate dielectric, characterized in that: It includes a substrate layer, a bottom gate electrode layer, a gate dielectric layer and a patterned electrode assembly arranged from top to bottom; The material of the substrate layer includes single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001); The bottom gate electrode layer includes a single crystal ZnSnO3 thin film; The gate dielectric layer includes a single crystal LiNbO3 or a single crystal LiTaO3 thin film.
2. The neuromorphic transistor with lithium niobate or lithium tantalate single crystal as gate dielectric according to claim 1, characterized in that: The thickness of the bottom gate electrode layer is 100 nm to 400 nm.
3. The neuromorphic transistor with lithium niobate or lithium tantalate single crystal as gate dielectric according to claim 1, characterized in that: The thickness of the gate dielectric layer is 100 nm to 2 μm.
4. The neuromorphic transistor with lithium niobate or lithium tantalate single crystal as gate dielectric according to claim 1, characterized in that: The patterned electrode assembly includes a channel layer, a source electrode, and a drain electrode; The channel layer is located between the source and the drain.
5. The neuromorphic transistor with lithium niobate or lithium tantalate single crystal as gate dielectric according to claim 1, characterized in that: The material of the channel layer is selected from N-type semiconductor materials; Preferably, the source and the drain are both low work function metal electrodes; Preferably, the material of the low work function metal electrode includes at least one of Au, Cr, Ni and Pt.
6. The method for preparing a neuromorphic transistor using lithium niobate or lithium tantalate single crystal as a gate dielectric according to any one of claims 1 to 5, characterized in that: The steps include: Providing a substrate layer including single crystal LiNbO3 (0001) or single crystal LiTaO3 (0001) material; A bottom gate electrode layer including a single crystal ZnSnO3 thin film is grown on the substrate layer by physical vapor deposition, and then a gate dielectric layer including a single crystal LiNbO3 or a single crystal LiTaO3 thin film is grown on the bottom gate electrode layer; A patterned electrode assembly is fabricated on the gate dielectric layer by sputtering.
7. The preparation method according to claim 6, characterized in that: The conditions for growing a single crystal include: preheating a substrate under vacuum conditions, then heat treating the substrate under oxygen pressure conditions, then performing physical vapor deposition on the substrate to obtain a target thin film and then performing in-situ annealing; The substrate is a substrate layer or a substrate layer deposited with a bottom gate electrode layer.
8. The preparation method according to claim 6, characterized in that: The preheating conditions include: heating the substrate to 450 °C ~500 °C at a heating rate of 5 °C / min ~20 °C / min and then maintaining it for 3 min ~5 min; Preferably, the oxygen pressure conditions include: continuously introducing oxygen with an oxygen pressure of 20 Pa to 30 Pa; Preferably, the heat treatment conditions include: heating the substrate to 600° C. to 700° C. and maintaining the temperature for 3 min to 5 min; Preferably, the in-situ annealing conditions include: adjusting the oxygen supply to reach atmospheric pressure, maintaining the heat treatment temperature for 30 min to 60 min, then cooling to 350° C. to 400° C., stopping the oxygen supply, and naturally cooling under vacuum conditions.
9. The preparation method according to claim 6, characterized in that: Physical vapor deposition is selected from pulsed laser deposition; The conditions of pulsed laser deposition include: the laser energy of the laser is 120 mJ ~140 mJ, and the frequency is 1 Hz ~3 Hz.
10. The preparation method according to claim 6, characterized in that: The process of making a patterned electrode assembly includes: Using N-type semiconductor material as target, radio frequency sputtering deposition forms a channel; Using low work function metal as the target, DC sputtering deposition is performed on both sides of the channel to form the source and drain.
Citation Information
Cited By
Ferroelectric memory and preparation method thereof
CN119866014A